RESPONS TANAMAN KAILAN (Brassica oleracea var. Alboglabra) PADA BERBAGAI KONSENTRASI AB MIX DENGAN SISTEM HIDROPONIK SUMBU (WICK SYSTEM) - Kartini ., Ali; Doortje M. F. Sumampow; Jeanne M. Paulus (Sam Ratulangi University, 2021)
This study aims to determine the response of kailan (Brassica oleracea var. Alboglabra) at various concentrations of AB Mix with the axis hydroponic system. The research was conducted in Islam Sub-District, Lingkungan V, Tuminting District, Manado City. This study was arranged in a Completely Randomized Design (CRD) with 4 (four) treatments, namely the concentration of AB Mix nutrients. All treatments were repeated 4 times, thus there were 16 research units. The data obtained from the observations were analyzed using the Analysis of Variance (ANOVA) at the 5% level and if the effect was significant, it was continued with the Least Significant Difference Test (BNT) at the 5% level. Processing and data analysis is done with the help of Microsoft software. Excel 2010. The results showed that the best concentration of AB Mix nutrients was obtained at a concentration of 1500 ppm.